Cities in a globalizing world governance, performance, and sustainability - edited by Frannie Léautier. (Washington World Bank, 2006)
Cities in a Globalizing World' stresses that quality of governance can determine whether the burgeoning cities of the developing world can become global centers of opportunity or urban examples of over crowding and underachievement.
Includes bibliographical references.
Keywords: Urban policy